APPLICATION OF 2-DIMENSIONAL TOMOGRAPHY TO INVESTIGATE SUBSURFACE LITHOLOGY IN AUCHI POLYTECHNIC, AUCHI, EDO STATE, NIGERIA (Nigerian Journal of Technology, 2020)
The Wenner – Schlumberger array was used for Constant Separation Traversing (CST) to investigate subsurface lithology in Auchi Polytechnic, Auchi. All the traverses were carried out with electrode spacing of 5 m with a spread of 200 m. The data was obtained using Pasi terrameter (16-GL) and processed with the Dipro software. The subsurface resistivity values ranged from 207 ?m – 8357 ?m. The results obtained from this survey classified the subsurface lithology into topsoil, clayey sand, sandy clay and sand. The maximum depth penetrated was 50 m. http://dx.doi.org/10.4314/njt.v39i3.31